A cross-product category CBBE study: item response theory perspective. Issue 3 (13th May 2014) - Wang, Luming; Finn, Adam
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this study is to propose a new item response theory-based model to facilitate brand equity comparison among brands in different product categories. Brand equity has been defined as the value a brand adds upon a product. This definition provides the theoretical basis for comparing brands across product categories. Researchers have measured brand equity from three major approaches: finance, economics and psychology. Unlike the first two approaches that have developed methods to facilitate cross-product-category brand equity comparison, no methodology has been identified in the psychology approach (consumer-based brand equity, CBBE), and this study will fill this gap. Design/methodology/approach – We used survey method and collected data from both soft drink and car product categories to empirically demonstrate our method. Findings – A new item response theory-based model to facilitate brand equity comparison among brands in different product categories is proposed. Originality/value – Considering consumers are the most widely considered stakeholder group in the existing brand equity literature, the lack of cross-product category research in consumer-based brand equity (CBBE) area constrains the use of CBBE for firms managing multiple brands across product categories. This proposed model is the first one to address this limitation.